Periodical publications - rare and bibliophile editions in the ﬁeld of Philology (Confluenţe Bibliologice, 2015)
Scientiﬁc Library USARB holds a collection of rare books, periodicals from XIX and XX century, 41 titles in 746 copies in the following languages: Romanian, French, German, Russian, Ukrainian. The majority publications were received as a donation on behalf of the Cultural Association „Pro Basarabia and Bucovina”, Galati Branch, Romania. Responsable for this is Radu Moţoc, engineer, the Secretary of Assosiation. This precious collection of magazines represents bibliophile rarities, literary and historical documents, which constitute a treasure for library.
Keywords: Rare periodical publications collection; cultural heritage